1987
DOI: 10.1038/329462a0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial relationship of the Fis binding sites for Hin recombinational enhancer activity

Abstract: Site-specific recombination reactions involve the joining or rearrangement of discrete DNA segments in a highly precise manner. A site-specific DNA inversion regulates the expression of flagellin genes in Salmonella by switching the orientation of a promoter. Analysis of the reaction has shown that, in addition to DNA sequences at the two boundaries of the 1-kilobase invertible segment where strand exchange occurs, another cis acting sequence is required for efficient inversion. This 60-base-pair enhancer-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 22 publications
0
58
0
Order By: Relevance
“…Fis also plays a very important role in several DNA inversion systems, enhancing the inversion rate up to 150-fold. In the Hin system, for example, Fis exerts its effect through a DNA enhancer element which has two Fis binding sites separated by 4.5 turns of the helix (15). This enhancer has also been found to function in a distanceand orientation-independent manner (15 (39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fis also plays a very important role in several DNA inversion systems, enhancing the inversion rate up to 150-fold. In the Hin system, for example, Fis exerts its effect through a DNA enhancer element which has two Fis binding sites separated by 4.5 turns of the helix (15). This enhancer has also been found to function in a distanceand orientation-independent manner (15 (39).…”
Section: Discussionmentioning
confidence: 99%
“…In the Hin system, for example, Fis exerts its effect through a DNA enhancer element which has two Fis binding sites separated by 4.5 turns of the helix (15). This enhancer has also been found to function in a distanceand orientation-independent manner (15 (39). Second, using the lambda infection assay to measure transposition at different stages of bacterial growth, we found that the peak of Fis stimulation occurred during the late exponential to early stationary growth phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Supercoil diffusion underpins many genetic processes including integration and excision (Gellert et al, 1976;Miller et al, 1981;Gellert and Nash, 1987), bacteriophage Mu transposition (Craigie and Mizuuchi, 1986), Tn3 and ␥␦-mediated site-specific resolution (Benjamin et al, 1985;Stark et al, 1989), site-specific inversion (Johnson et al, 1987;Heichman and Johnson, 1990;Kanaar et al, 1990) and doubtless many other processes that involve DNA loops (Adhya, 1989;Eismann and Muller-Hill, 1990;Lobell and Schleif, 1990;Matthews, 1992;Haykinson and Johnson, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Hin protein and the hixL and hixR sites, the inversion reaction requires a DNA recombinational enhancer site and two other cell proteins, Fis and HU (Johnson and Simon 1985;Johnson et al 1986). The Fis protein interacts directly with the enhancer, whereas the HU protein is thought to contribute to the efficiency of the recombination reaction by enhanced bending of the DNA (Bruist et al 1987a;Johnson et al 1987). All of these factors orchestrate the formation of a specific protein-DNA complex necessary for the breakage and rejoining of DNA at the hixL and hixR sites resulting in inversion (Bruist et al 1987b).…”
mentioning
confidence: 99%